Strategies to Realize Prosperity for Provinces With Islands in Indonesia. Issue 1 (1st October 2022) - Adhayanto, Oksep; Nazaki; Rahmawati, Nanik; Arianto, Bismar; Suwardi, Nurhasanah; Subiakto, Rudy; Suryadi; Darmawan, Eki; Pratama, Ryan Anggria
Abstract: The purpose of this research is to formulate a strategy for the welfare of the people in the archipelago by increasing funds in the regions. Currently, there are still many problems faced by the provincial government, which is an archipelagic province with many marine resources but little distribution of general allocation funds. These include poverty and welfare issues. A special approach is needed to overcome this problem by finding solutions based on laws and regulations. This type of research is descriptive qualitative with a literature and legislation approach. The conclusion of this research, first, it is necessary to reformulate the calculation of the general allocation fund which includes the sea area as an indicator of the calculation. Second, urging the ratification of local government regulations on islands as mandated in local government laws. Third, accelerate the discussion and ratification of the Archipelago Bill.